Modified monopole ring antennas as a solution for HiperLAN1/2 and IEEE 802.11b/g standard devices - Anna Miskiewicz; Marek Kitliński (Journal of Telecommunications and Information Technology, 2023)
A compact planar antenna for multisystem ap- plications has been designed and manufactured. A modified feeding method has been used to meet the requirements of modern telecommunications devices. It has been shown, that by adjusting the size of the rings, required allocation of bands is possible. The proposed antenna is suitable for ISM band devices and gives perspectives for multi-standard operation. The antenna has been simulated using MoM 2.5D software Zeland IE3D, next fabricated and measured.